Use of ultrasound-measured internal jugular vein collapsibility index to determine static intracardiac pressures in patients with presumed pulmonary hypertension - Parikh, Raj (Ann Intensive Care, 2019)
BACKGROUND: Bedside ultrasound helps to estimate volume status in critically ill patients and has traditionally relied on diameter, respiratory variation, and collapsibility of the inferior vena cava (IVC) to reflect fluid status. We evaluated collapsibility of the internal jugular vein (IJ) with ultrasound and correlated it with concomitant right heart catheterization (RHC) measurements in patients with presumed pulmonary hypertension. METHODS AND RESULTS: We studied 71 patients undergoing RHC for evaluation of pulmonary hypertension. Using two-dimensional ultrasound (Sonosite, Washington, USA), we measured the diameter of the IJ at rest, during respiratory variation, and during manual compression. Collapsibility index during respiration (respiratory CI) and during manual compression (compression CI) was calculated. We correlated mean right atrial pressure (mRAP) and pulmonary artery occlusion pressure (PAOP) defined by RHC measurements with respiratory and compression CI. A secondary goal was examining correlations between CI calculations and B-type natriuretic peptide (BNP) levels. Baseline characteristics demonstrated female predominance (n = 51; 71.8%), mean age 59.5 years, and BMI 27.3. There were significant correlations between decrease in compression CI and increase in both mRAP (Spearman: − 0.43; p value = 0.0002) and PAOP (Spearman: − 0.35; p value = 0.0027). In contrast, there was no significant correlation between respiratory CI and either mRAP (Spearman: − 0.14; p value = 0.35) or PAOP (Spearman:− 0.12; p value = 0.31). We also observed significant negative correlation between compression CI and BNP (Spearman: − 0.31; p value = 0.01) but not between respiratory CI and BNP (Spearman: − 0.12; p value = 0.35). CONCLUSION: Increasing use of ultrasound has led to innovative techniques for estimating volume status. While prior ultrasound studies have used clinical parameters to estimate fluid status, our study used RHC measurements and demonstrated that compression CI potentially reflects directly measured mRAP and PAOP.